Bone marrow adipocytes: key players in vascular niches, aging, and disease - Fan, Yonggang; Elkhalek, Mai; Zhang, Yuheng; Liu, Lu; Tian, Qi; Chueakula, Nareekarn; Ramasamy, Saravana K.; Dalan, Rinkoo; Habib, Shukry J.; Kusumbe, Anjali P. (Frontiers in Cell and Developmental Biology, 2025)
Bone marrow adipocytes (BMAs) are emerging as metabolically active endocrine organs within the bone marrow microenvironment, engaging in extensive crosstalk with vascular niches, osteogenic cells, and hematopoietic compartments. In aging and metabolic disorders, mesenchymal and adipocyte progenitors undergo significant quantitative and qualitative transformations that shift from osteogenesis toward adipogenesis. This enhanced adipogenic profile alters the secretion of key adipokines and cytokines, thereby impairing endothelial function, destabilizing the vascular niche, and reducing hematopoietic stem cell support—culminating in bone fragility and disrupted blood cell production. Central to these alterations are pivotal signaling pathways, which orchestrate the interplay between BMAs and their surrounding cells. Furthermore, factors like oxidative stress, chronic inflammation, and endocrine dysregulation modulate BMA behavior and exacerbate their impact on marrow homeostasis. In this comprehensive review, we integrate recent advances that elucidate the molecular and cellular mechanisms underlying BMA function and their complex interactions with vascular niches. We also discuss therapeutic strategies designed to modulate BMA-mediated pathways and their downstream effects on aging and a range of diseases.